(untitled) (Huellas, 2024)
In Argentina, within the framework of the energy transition, transformations to diversify the energy production matrix are promoted. This article explores, through the collection of secondary data, innovative experiences that give new meaning to energy projects from different sources on productive, cultural, touristic and environmental enhancement. To analyze the gathered experiences, the data was produced from the following categories: local initiatives, public-private management and socio-technical changes. The results yielded links with educational, productive, tourist and/or environmental scenarios. Likewise, it is inferred that the enhancement of energy heritage contributes to give visibility to strategic resources and systems for the well-being of populations and territorial dynamics.